Clean process for vanadium extraction from vanadium-bearing converter slag. Issue 1 (February 2023) - Yao, Zhichao; Yu, Jiancheng; Ma, Baozhong; Wang, Ling; Wang, Chengyan; Wang, Baohua; Gao, Minglei; Feng, Guosheng
Abstract: The clean extraction of vanadium from vanadium-bearing converter slag (VBCS) has important implications for the sustainable development of the vanadium industry. In this work, a process that included sieving, nonsalt roasting, and sulfuric acid leaching was carried out to extract vanadium from VBCS. First, through sieving, large particles of metallic iron were removed and vanadium with particle sizes of less than 150 µm was preliminarily enriched. Subsequently, the nonsalt roasting process was investigated in terms of the effects of temperature and time and the phase transformation mechanism. The structures of vanadium ferrospinel and fayalite were destroyed completely after roasting at 900 °C for 1.5 h, and vanadate, Fe2 O3, SiO2, and Fe2 TiO5 formed in the roasted product. Finally, the systematic sulfuric acid leaching experiment demonstrated that over 97% of vanadium was extracted under optimal conditions. Meanwhile, the phase analysis of the leaching residue confirmed that vanadate was selectively leached into the solution. Highlights: A clean process for extracting vanadium from vanadium-bearing converter slag was studied. The migration law of components in nonsalt roasting was revealed. Over 97% of vanadium was selectively extracted by sulfuric acid leaching. The leaching residue does not contain alkali metals and can be reused.